Penyuluhan Hukum tentang Hak-Hak Anak di Lembaga Pembinaan Khusus Anak Kelas 1 Tangerang oleh LKBH FH UPH: Legal Counseling on Children's Rights at the Tangerang Grade 1 Special Child Development Institution by LKBH FH UPH - Rizky Karo Karo; Vincensia Esti Purnama Sari; Hosiana Daniel Adrian Gultom; Sharon Rheinata; Serlly Waileruny; Yoshin Nainggolan; Steven Steven; Bernice Bernice (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
The Institute for Legal Consultation and Assistance, Faculty of Law, Universitas Pelita Harapan (FH UPH) provides community service in the form of legal counseling to foster children, children serving sentences at Child special development institution LPKA Class 1 Tangerang, and to remind children that they must be prepared to return to society. This PKM activity is the first activity conducted at LPKA Class I Tangerang in 2022, and it is the implementation of a cooperation agreement between the UPH Faculty of Law and Class I LPKA Tangerang that began in November 2022. This PKM activity was conducted on 10 November 2022 with the participation of 20 fostered children and 5 State Civil Apparatusa in an LPKA Class I Tangerang environment. This action is conducted in accordance with health standards to prevent the spread of the Covid-19 virus in LPKA.